THE USE OF REDUPLICATED ADJECTIVES IN CONTEMPORARY NOVELS - Irene Pabuntang; Aryana N Qarimah (Universitas Sam Ratulangi, 2025)
Reduplication adjectives are widely used in contemporary novels to show beauty. This study aims to determine the use of reduplication adjectives in contemporary novels. The data sources are sentences containing reduplication adjectives in three contemporary novels with the titles